THE INFLUENCE OF ISLAMIC COUNSELING ON THE DEVELOPMENT OF VIRTUOUS CHARACTER IN STUDENTS - Sugiyanto Sugiyanto; Citra Aulia Uzliva; Almaydza Pratama Abnisa (Sekolah TInggi Ilmu Dakwa dan Komunikasi Islam (STIDKIS) Al Mardliyyah Pamekasa, 2025)
The development of virtuous character in students is influenced by discipline, integrity, educational environment, and Islamic counseling, which fosters morality, responsibility, empathy, and religious awareness comprehensively. This study aims to analyze the effectiveness of Islamic counseling in enhancing virtuous character among vocational high school students, including honesty, discipline, responsibility, tolerance, empathy, and the application of Islamic values in daily life. The research employed a quantitative approach with a One-Group Pretest-Posttest experimental design, collecting data through questionnaires and observation. The results indicate that the regression test showed a significance value (Sig.) for the Pretest coefficient of 0.000, which is smaller than 0.05, indicating a significant influence of the initial scores on the Posttest outcomes. In other words, the students’ initial character conditions before counseling significantly affected the development of virtuous character after the intervention. These findings reinforce that Islamic counseling is effective in shaping virtuous character, assisting students in increasing awareness, motivation, and the application of values such as honesty, trustworthiness, and patience, thereby producing consistent positive behavioral changes post-intervention. Conclusion: Islamic counseling can significantly influence the formation of noble character in students.